Effect of formulated bioorganic containing Burkholderia GanoEB2 in suppressing Ganoderma disease in oil palm seedlings - Norsilan Ili Nadhrah; Rosimah Nulit; Ramli Nurrashyeda; Abu Seman Idris (Plant Protection Science, 2015)
The ability of Burkholderia GanoEB2 formulated in two different bioorganic powders as carriers - bioorganic empty fruit bunch (BEFB) and real strong bioorganic fertilizer (RSBF), and the efficacies of Burkholderia GanoEB2 in suppressing Ganoderma boninense infection in oil palm seedlings were determined. Results showed that the highest reduction in disease incidence (DI, 18.2%), severity of foliar symptoms (SFS, 26.6%), and disease severity foliar index (DSFI, 27.7%) was achieved by the seedlings treated with RSBF containing Burkholderia GanoEB2 compared to the seedlings treated with BEFB containing Burkholderia GanoEB2 (36.4% DI, 33.4% SFS, and 31.8% DSFI). Untreated seedlings (as control) had 100.0% DI, 90.4% SFS, and 87.5% DSFI. The disease was reduced by as much as 85.3% for seedlings treated with RSBF and by 70.5% for seedlings treated with BEFB. The formulated bioorganics containing Burkholderia GanoEB2 were proven to suppress Ganoderma disease in oil palm.